Tailoring Multidimensional Traps for Rewritable Multilevel Optical Data Storage - Liu, Dong; Yuan, Lifang; Jin, Yahong; Wu, Haoyi; Lv, Yang; Xiong, Guangting; Ju, Guifang; Chen, Li; Yang, Shihe; Hu, Yihua (ACS applied materials & interfaces, 2019)
In the current “big data” era, the state-of-the-art optical data storage (ODS) has become a front-runner in the competing data storage technologies. As one of the most promising methods for breaking the physical limitation suffered by traditional ones, the advance of optically stimulated luminescence (OSL) based optical storage technique is now still limited by the simultaneous single-level write-in and readout in a same spot. In this work, to bridge the data-capacity gap, we report for the first time a novel and promising nonphysical multidimensional OSL-based ODS flexible medium for erasable multilevel optical data recording and reading. We tailor multidimensional traps with discrete, narrowly distributed energy levels through (multi-)codoping of selective trivalent rare-earth ions into Eu2+-activated barium orthosilicate (Ba2SiO4). Upon UV/blue light illumination, information can be sequentially recorded in different traps assisted by thermal cleaning with an increase of storage capacity by orders of magnitude, which is addressable individually in the whole domain or bit-by-bit mode without the crosstalk by designed thermal/optical stimuli. Remarkably, good data retention and robust fatigue resistance have been achieved in recycle data recording. Insight is forged from charge carrier dynamics and interactions with traps for a universal method of data storage, and proof-of-concept applications are also demonstrated, thereby providing the way to not only rewritable multilevel ODS but also high-security encryption/decryption.